EKSTRAKSI STRUKTUR PENDUDUK KOTA PADANG PANJANG TAHUN 2017-2021 (Jurnal Spasial, 2023)
The population structure in an area can be seen from the population data, population distribution, and how the composition of the population in the area. With this population data, it can be used as a reference in making decisions by the government in setting policies. In order to get the right policy, an analysis of these data must be carried out. One of the analyzes that can be done is population structure analysis. The population structure analysis was carried out in the city of Padang Panjang with the analytical parameters in the form of population composition, fertility, sex ratio, and level of dependence. This study aims to determine the distribution of the population of the city of Padang Panjang in 2017-2021 according to Fertility, Sex Ratio, and Dependency Ratio. The analysis was carried out descriptively on tables and population pyramids of Padang Panjang City in 2017-2021. The results show that the population pyramid of the city of Padang Panjang has an expansive shape which shows that the city of Padang Panjang is dominated by the population of the young age group. The value of the Dependency ratio of the City of Padang Panjang within a period of 5 years, namely 2017-2021, has a downward trend. The year 2017 shows the dependency ratio value of 54,6. This shows that as many as 54 to 55 non-productive residents must be borne by 100 productive residents, in 2021 the decrease in the dependency ratio of Padang Panjang City reaches 48,0.